The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/0014-5793(96)00187-1
|View full text |Cite
|
Sign up to set email alerts
|

The H+‐ATPase purified from maize root plasma membranes retains fusicoccin in vivo activation

Abstract: The activity of 'P-type' ATPases is modulated through the C-terminal autoinhibitory domain. The molecular bases of this regulation are unknown. Their understanding demands functional and structural studies on the activated purified enzyme. In this paper the plasma membrane H+-ATPase from maize roots activated in vivo by fusicoccin was solubilised and fractionated by anion-exchange HPLC. Results showed that the H+-ATPase separated from fusicoccin receptors retained fusicoccin activation and that it was more evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Purification of H ϩ -ATPase from Maize Roots-Two-phase partitioned plasma membranes were obtained from 200 g of maize roots as described previously (26). When indicated, plasma membranes were treated with 0.5% Triton X-100 (26).…”
Section: Methodsmentioning
confidence: 99%
“…Purification of H ϩ -ATPase from Maize Roots-Two-phase partitioned plasma membranes were obtained from 200 g of maize roots as described previously (26). When indicated, plasma membranes were treated with 0.5% Triton X-100 (26).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been demonstrated that FC in vivo treatment of plant tissues, which produces a strong stimulation of H ϩ -ATPase activity, concomitantly brings about a marked increase in plasma membraneassociated 14-3-3 proteins (4,11). Also, the amount of FC bound to plasma membrane appears to be strictly correlated with stimulation of H ϩ -ATPase activity (12).…”
mentioning
confidence: 99%
“…Purification of H ϩ -ATPase-H ϩ -ATPase from maize roots was solubilized from two-phase partitioned plasma membranes and purified by anion-exchange HPLC as previously described (11). To obtain C-terminally truncated H ϩ -ATPase, before purification, plasma membranes were treated with trypsin under the conditions described by RasiCaldogno et al (19).…”
mentioning
confidence: 99%
“…Santos) from Dekalb (Mestre, Italy) were germinated and grown in the dark for 6 days as already described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Maize Plasma Membranes-Two-phase partitioned plasma membranes from maize roots were obtained as described previously (18).…”
Section: Methodsmentioning
confidence: 99%